Pengaruh Aplikasi Penyiraman Air Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah Varietas Pancasona dan Tss Agrihorti-2 - Achmad Julfikar; Wagiono Wagiono; H.M. Yamin Samaullah; Prasodjo Soedomo (Peneliti.net, 2021)
Onion cultivation depends on soil fertility levels and watering sources that fit the needs of plants as well as the lack of available land in urban make plantings done with a polybag scale scope so that the results of plant responses to water needs can be seen based on these aspects of physiology, morphology, growth rates, as well as productivity. As for the variety type differences in the cultivation process in a different growing environment can provide the best picture of the variety type results that can be cultivated according to their growing ability and growing environment influence. Research is implemented in the Vegetable Plant Research Hall experimental garden screenhouse located in Cikole Village, Lembang Subdistrict, West Bandung County. In September to December 2020. The research method used is the experimental method using the Group Random Design (RAK) factorial. There are two factors with 4 treatments each repeated 6 times so there are 24 units of experiments. The effect of treatment is analyzed with the variety print and when F test is 5% significant, then to know the treatment best continued with the DMRT (Duncan Multiple Range Test) follow-up test at 5% degree. he results of the study showed that there was no effect of interaction between watering applications of water with the type of onion varieties. But there is a self-contained influence of watering applications and types of onion varieties on some research parameters. The treatment of p2 water water watering application (every 2 days watering) gives the highest yield to the diameter of the tuber (16.29 mm). As for onion treatment the variety Agrihorti-2 (d2) gives the highest yield at plant height (35.76 cm), long (5.83 mm). And for onions the variety of pancasona (d1) gives the highest yield at the diameter of the tuber (15.69 mm).